Impact of enhanced recovery protocols after pancreatoduodenectomy: meta-analysis. Issue 3 (17th January 2022) - Kuemmerli, Christoph; Tschuor, Christoph; Kasai, Meidai; Alseidi, Adnan A; Balzano, Gianpaolo; Bouwense, Stefan; Braga, Marco; Coolsen, Mariëlle; Daniel, Sara K; Dervenis, Christos; Falconi, Massimo; Hwang, Dae Wook; et al.
Abstract: Background: This individual-patient data meta-analysis investigated the effects of enhanced recovery after surgery (ERAS) protocols compared with conventional care on postoperative outcomes in patients undergoing pancreatoduodenectomy. Methods: The Cochrane Library, MEDLINE, Embase, Scopus, and Web of Science were searched systematically for articles reporting outcomes of ERAS after pancreatoduodenectomy published up to August 2020. Comparative studies were included. Main outcomes were postoperative functional recovery elements, postoperative morbidity, duration of hospital stay, and readmission. Results: Individual-patient data were obtained from 17 of 31 eligible studies comprising 3108 patients. Time to liquid (mean difference (MD) −3.23 (95 per cent c.i. −4.62 to −1.85) days; P < 0.001) and solid (−3.84 (−5.09 to −2.60) days; P < 0.001) intake, time to passage of first stool (MD −1.38 (−1.82 to −0.94) days; P < 0.001) and time to removal of the nasogastric tube (3.03 (−4.87 to −1.18) days; P = 0.001) were reduced with ERAS. ERAS was associated with lower overall morbidity (risk difference (RD) −0.04, 95 per cent c.i. −0.08 to −0.01; P = 0.015), less delayed gastric emptying (RD −0.11, −0.22 to −0.01; P = 0.039) and a shorter duration of hospital stay (MD −2.33 (−2.98 to −1.69) days; P < 0.001) without a higher readmission rate. Conclusion: ERAS improved postoperative outcome after pancreatoduodenectomy. Implementation should be encouraged. Lay Summary: Enhanced recovery protocols consist of interdisciplinary interventions aimed at standardizing care and reducing the impact of surgical stress. They often include a short period of preoperative fasting during the night before surgery, early removal of lines and surgical drains, early food intake and mobilization out of bed on the day of surgery. This study gives a summary of reports assessing such care protocols in patients undergoing pancreatic head surgery, and assesses the impact of these protocols on functional recovery in an analysis of individual-patient data. The study revealed the true benefits of enhanced recovery protocols, including shorter time to food intake, earlier bowel activity, fewer complications after surgery, and a shorter hospital stay compared with conventional care. Abstract : This meta-analysis investigated the impact of enhanced recovery protocols in patients undergoing pancreatoduodenectomy compared with conventional care. The benefits regarding functional recovery elements are a shorter time to oral intake, recovery of bowel function, and surgical drain removal as well as a lower postoperative complication rate and shorter hospital stay, without increasing the readmission rate. In view of these benefits, the implementation of such programmes should be encouraged in all centres performing pancreatoduodenectomy.